Penokohan dalam Lakon Maut dan Sang Dara - Wenhendri Wenhendri; Edy Suisno (Institut Seni Indonesia Padangpanjang, 2025)
This research “Characterization of Characters in Ariel Dorfman’s Maut dan Sang Dara (Death and Maiden; trans. Mimi Notokusumo) is a study of characters in the play by emphasizing the reading and reflection on the speech and actions of each character. This study is also to see the uniqueness of each character especially in determining the existence of main character and its relation with another characters. Opposing or supporting relationship of each characters is described in relation to the main conflict of the play. The research begins with a ‘three-dimensional reading’ by examining their identities physically, psychologically, and sociologically. This step is followed up by exploring the various emotions, thoughts, and actions of the main characters as a result of the emotions, thoughts, and actions of the other characters. Ultimately, the reading of characters in Maut dan Sang Dara sees and finds differences in each character which then sharpens and deepens the conflict in the story. Maut dan Sang Dara, Ariel Dorfman, Characterization, and Relation of character.